Evaluation of BOSEH (Bike on the Street Everybody Happy) Program in Bandung City - Aria Mahendra Chandra; Mudiyati Rahmatunnisa; Slamet Usman Ismanto (Universitas Muhammadiyah Malang, 2025)
The bike sharing program in Bandung City known as